Soil salinity increases survival of freezing in the enchytraeid Enchytraeus albidus - Patrício Silva, A. L.; Holmstrup, M.; Košťál, V. (Vladimír); Amorim, M. J. B. (Journal of Experimental Biology, 2013)
Enchytraeus albidus is a freeze-tolerant enchytraeid found in diverse habitats, ranging from supralittoral to terrestrial and spanning temperate to arctic regions. Its freeze tolerance is well known but the effect of salinity in this strategy is still poorly understood. We therefore studied the combined effect of salinity and sub-zero temperatures on the freeze tolerance of E. albidus collected from two distinct geographical regions (Greenland and Germany). Worms exposed to saline soils had an improved survival of freezing compared to worms frozen in non-saline soils. Differential scanning calorimetry measurements showed that the fraction of water frozen at −5 and −14°C was lower in worms exposed to 35> NaCl than in control worms. The lowering of ice content by exposure to saline soils was probably the main explanation for the better freeze survival in saline-exposed worms.